Figure 4 from: Jung J, Alfonsi E, Méheust E, Fuchs S, Carpentier F, Quillivic Y, Viricel A, Hassani S (2013) The use of DNA barcoding to monitor the marine mammal biodiversity along the French Atlantic coast. ZooKeys 365: 5-24. https://doi.org/10.3897/zookeys.365.5873 - Alfonsi, Eric; Méheust, Eleonore; Fuchs, Sandra; Carpentier, François-Gilles; Quillivic, Yann; Viricel, Amélia; Hassani, Sami; Jung, Jean-Luc (Zenodo, 2013)
Figure 4 - Examples of marine mammals stranded along the coasts of Brittany and the species-level identifications of which were determined or confirmed thanks to DNA barcoding. A Sample Ms250511, stranded on the "Île de Sein" during May 2011, and identified as a Balaenoptera physalus B Sample Ds160111, stranded on the Ushant Island during January 2011, and identified as a Grampus griseus C Sample Ds130211, stranded on the Ushant Island in February 2011, and identified as belonging to the Delphininae subfamily (putatively identified as a Delphinus delphis on the nMDS plot in Figure 5) D Sample Ds080410 stranded on the Ushant Island during April 2010, and identified as belonging to the Delphininae (putatively identified as a Stenella coeruleoalba on the nMDS plot in Figure 5).